Analisis Poros Engkol (Connecting Rod) Sepeda Motor 110 CC Menggunakan Material Baja AISI 1045 - Sukroni; Leo Van Gunawan; Tito Endramawan (CV. Multi Kreasi Media, 2023)
Motorcycles with a capacity of 110 cc are often used for racing in Indonesia. The high and repetitive pressure that the piston receives during compression creates a fatigue load on the connecting rod. It some cases, connecting rod can be buckling or fracture at critical part because it is not strong to endure fatigue load from piston. To anticipate occurrence of buckling and fracture, it is necessary to choose a strong material to endure fatigue load in connecting rod. The type of material that can used for design of connecting rod is AISI 1045 Steel. AISI 1045 Steel is a type of steel that can be used to manufacture vehicle engine component such as gears, shafts and connecting rods. To find out the amount of deformation and maximum stresses on the connecting rod using AISI 1045 Steel needed simulation with Finite Element Methode (FEM) in Solidworks. The results of simulation analysis show that the maximum stress is 1,996x101 N/mm2 (MPa). Maximum stress does not exceed the yield strength limit of AISI 1045 Steel. Maximum deformation get a 1,489x10-2 mm so the deformed shape in the connecting rod is very small. Factor of Safety (FoS) get a 26,5 this indicate if design of connecting rod with AISI 1045 Steel is safe to use.